THE EFFECTIVENESS OF EDUCATION THROUGH VIDEO MEDIA ON THE KNOWLEDGE, ATTITUDES, AND BEHAVIOR OF HYPERTENSION PATIENTS IN THE WORKING AREA OF THE PALEMBANG CITY HEALTH CENTER - Racellyta, Dwinisa Dea; Intan Kumalasari; Faiza Yuniati (Indonesia Epidemiological Journal, 2025)
Background: Hypertension is a non-communicable disease often referred to as the "silent killer" due to its asymptomatic nature and potential to cause severe complications. In Indonesia, including the city of Palembang, the prevalence of hypertension continues to rise, highlighting the urgency of effective health education as a preventive measure.Objective: This study aims to evaluate the effectiveness of educational interventions delivered via video media in improving the knowledge, attitudes, and practices of hypertensive patients within the service area of the Pembina Community Health Center, Palembang. Method: A quasi-experimental design with a one-group pre-test and post-test approach was employed. A total of 109 respondents were selected using purposive sampling. Data were collected using validated questionnaires measuring knowledge, attitude, and behavior, with reliability coefficients ranging from 0.689 to 0.878. Data analysis was conducted using univariate and bivariate methods, including the Wilcoxon Signed-Rank Test. Results: The intervention significantly improved participants' knowledge, attitudes, and practices regarding hypertension management, as indicated by p-values ranging from 0.000 to 0.002. The mean knowledge score increased from 70.18 to 84.42, the mean attitude score from 84.95 to 89.43, and the mean practice score from 72.11 to 83.22. The percentage increases for each variable were 14.24% for knowledge, 4.48% for attitude, and 11.09% for behavior. Conclusion: The educational intervention using video media effectively enhanced the knowledge, attitude, and behavior of hypertensive patients, as evidenced by statistically significant improvements in all measured domains (p < 0.05). Recommendation: Educational videos are recommended as an effective strategy for health promotion and hypertension prevention, as they provide clear, visual information that can support behavioral change among patients